Older adults' eHealth literacy and the role libraries can play. (September 2021) - Lin, Zhenping; Zhang, Yao; Matteson, Miriam; Li, Xiaoming; Tu, Xiaoming; Zhou, Yeqin; Wang, Jing
This study examined the eHealth literacy, health knowledge, health behavior of a population of older Chinese adults, and the impact of using library or community activities for health information seeking. A survey was conducted among 215 participants 45 years or older. Data were analyzed using chi-square test, one-way analysis of variance, bivariate correlation, and multiple regression. The results showed that participants who were urban residents, non-farm workers, and had 9 years of education or more were more likely to use the library or community activities for health information seeking. Health behavior had a significant relationship with eHealth literacy and health knowledge. Both eHealth literacy and health knowledge showed a significant positive relationship with using the library or community activities for health information. These results support the idea that libraries play an important role in providing high-quality eHealth literacy services to enhance healthy behavior and health outcomes in their communities.